2008
DOI: 10.1182/blood-2008-01-134692
|View full text |Cite
|
Sign up to set email alerts
|

Central role of PI3K in transcriptional activation of hTERT in HTLV-I–infected cells

Abstract: The persistence of human T-cell leukemia/ lymphoma virus-I (HTLV-I)-infected cells is dependent upon clonal expansion and upregulation of telomerase (hTERT). We have previously found that in interleukin (IL)-2-independent transformed HTLV-I cells, Tax strongly activates the hTERT promoter through nuclear factor-B (NF-B)-mediated Sp1 and c-Myc activation. In IL-2-dependent cells and adult T-cell leukemia/ lymphoma (ATLL) patient samples, however, Tax expression is very low toundetectable, yet these cells retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 38 publications
2
39
0
2
Order By: Relevance
“…IL-2 signaling has recently been shown to be associated with the upregulation of the hTERT promoter in Taxnegative HTLV-1-transformed cells (12). These findings suggest that telomerase is an attractive target for anticancer drug discovery in ATL; however, the mechanism of IL-2-dependent telomerase activation in Tax-negative ATL tumor cells has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…IL-2 signaling has recently been shown to be associated with the upregulation of the hTERT promoter in Taxnegative HTLV-1-transformed cells (12). These findings suggest that telomerase is an attractive target for anticancer drug discovery in ATL; however, the mechanism of IL-2-dependent telomerase activation in Tax-negative ATL tumor cells has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 51%
“…This mechanism is different from what was observed in NK cell tumors, in which mTOR and HSP90 are only implicated in the posttranslational regulation of hTERT (32). Recently, Bellon and colleagues reported that IL-2 signaling is associated with PI3K-dependent transcriptional upregulation of hTERT through the suppression of WT-1 in Taxnegative HTLV-1-transformed cells (12). This mechanism might also contribute to the IL-2-induced telomerase activity observed in this ATL system, even in the absence of Tax protein.…”
Section: Discussionmentioning
confidence: 67%
“…La tendencia a la integración subtelomérica y telomérica registradas en el meta-análisis, pueden ser determinantes de la estabilidad cromosómica y la carcinogénesis (26). En el LLCTA se detiene el acortamiento crítico por la activación de la Telomerasa y de sus proteínas de enlace (TRF1, TRF2 y TIN2) (27).…”
Section: Discussionunclassified
“…10 In HTLV-I-infected cells and ATL tumor cells, Tax or interleukin-2 (IL-2) signaling strongly activates the hTERT promoter through the nuclear factor-kB or PI3K pathway, [11][12][13] suggesting that expression of hTERT protein would be upregulated in ATL tumor cells. Clinical trials of anticancer immunotherapy targeting hTERT have already been conducted, and both the safety and induction of immune responses to hTERT have been reproducibly confirmed.…”
Section: Introductionmentioning
confidence: 99%